Next-generation hybrid nanogenerators using giant piezoelectric lead-free KNNS composites for sustainable self-powered electronics - Sumang, Rattiphorn; Charoonsuk, Thitirat; Bongkarn, Theerachai; Chiu, Te Wei; Vittayakorn, Naratip; Panpho, Phakakorn (My University, 2025)
This study presents a flexible hybrid nanogenerator that utilizes lead-free KNNS-BF-xBNZ materials integrated with polydimethylsiloxane (PDMS) to enhance energy harvesting performance. The findings demonstrate that by combining piezoelectric and triboelectric effects, the energy conversion efficiency of the nanogenerator is significantly improved, resulting in high output voltage and current, suitable for real-world applications. Specifically, the optimal composition of KNNS-BF-xBNZ ceramics, with x = 0.03 mol.%, yields superior piezoelectric, ferroelectric, and dielectric properties, with remnant polarization (Pr), spontaneous polarization (Ps), and piezoelectric coefficient (d33) values reaching 18.8 μmC/cm², 30.3 μmC/cm², and 358 pC/N, respectively. In the hybrid device, incorporating 15 wt% of KNNS-BF-3BNZ into PDMS resulted in the highest open-circuit voltage (VOC) of 107 V and short-circuit current (ISC) of 4.68 μA. The developed hybrid nanogenerator effectively charges capacitors for energy storage, powers LEDs, and drives small electronic devices, such as watches, showcasing its potential for practical energy harvesting applications. The findings suggest that the integration of KNNS-BF-3BNZ with PDMS provides an efficient and scalable pathway for fabricating high-performance nanogenerators, paving the way for advancements in self-powered devices and sustainable energy solutions.
Keywords: Hybrid nanogenerator; Lead-free KNNS-BF-xBNZ; Piezoelecric properties; Self-powered electronics; Triboelectric properties